MODIFICACIONES EN EL ESTADO DE ESFUERZOS Y CALCULO DE LA CAPACIDAD DE CARGA ADMISIBLE DE UNA TOBA METEORIZADA, SANTO DOMINGO, HEREDIA, COSTA RICA: CASO CIMENTACION CIRCULAR - Mora Ch., Rolando (2011)
This study shows the classification of the weathering products of tuffs,using geotechnical criteria. The main physical properties of the material have been determined as well. The geostatic and induced stresses have been calculated in the case of a circular foundation, determining the most suitable exploration depth and the limiting depth tobe used in calculating the expected settlement. The allowable bearing capacity of the mate-rial has been calculated with the use of the shear resistance parameters, as a function of thediameter and depth of foundation.